Prior entrepreneurship exposure and work experience as determinants of entrepreneurial intentions among South African university of technology students - Malebana, Mmakgabo Justice; Mahlaole, Simon Thabo (Frontiers in Psychology, 2023)
Purpose This study used the theory of planned behaviour to investigate the effects of prior entrepreneurship exposure and work experience on entrepreneurial intentions among students at a South African university of technology. Design/methodology/approach Data was gathered using an online survey questionnaire and convenience sampling. The online survey was completed by 301 entrepreneurship diploma students from the Tshwane University of Technology, and the data were analysed using Smart-PLS 4. Findings The findings of this study revealed that prior work experience has a positive and statistically significant relationship with subjective norms and an insignificant relationship with perceived behavioural control, attitude towards behaviour and entrepreneurial intentions. Prior entrepreneurship exposure had a negative but statistically significant relationship with entrepreneurial intentions, subjective norms, attitude towards behaviour and perceived behavioural control. The relationship between prior entrepreneurship exposure and entrepreneurial intentions was partially mediated by subjective norms, attitude towards behaviour and perceived behavioural control. The findings further revealed that perceived behavioural control, subjective norms and attitude towards behaviour had a positive and statistically significant relationship with entrepreneurial intentions. Originality The study tested the effects of both prior entrepreneurship exposure and work experience on entrepreneurial intentions and its antecedents which have not been explored fully in previous research. Thus, the study advances the theory of planned behaviour as a model for testing the role of prior entrepreneurship exposure and work experience in the formation of entrepreneurial intentions in the South African context.